EFEKTIVITAS TEPUNG BUNGA KECOMBRANG (Nicolaia speciosa Horan) SEBAGAI PENGAWET TERHADAP SIFAT FISIK DAGING BROILER - Laras Gusniati Prabowo; Rr. Riyanti; Veronica Wanniatie (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This study aims to: 1 ) study the effect of kecombrang (Nicolaia speciosa Horan) flower powder on the physical properties consistif of the texture , water holding capacity , and cooking loss meat broiler, 2) knowing the best dose kecombrang (Nicolaia speciosa Horan) flower powder as a preservative broiler meat . Research was conducted on 8 September 2015 in Laboratory Animal Production and Reproduction Univeritas Lampung while for the analysis of physical properties of broiler meat made ​​on 9 September 2015 at the Laboratory of Agricultural Technology , Politeknik Negeri Lampung. The method used completely randomized design (CRD) , consisting of 4 treatments and 5 replications. Treatments are: 1) P0: 0% kecombrang flower powder rate; 2) P1: 2 % kecombrang flower powder; 3) P2: 4 % kecombrang flower powder; 4) P3: 6 % kecombrang flower powder. Data were analyzed variance at 5%. If the results of the analysis show real results , then the test continued with Least Significant Difference (LSD) at 5%. The results showed that administration of kecombrang flower powder on broiler meat significantly (P<0,05) water holding capacity and cooking losses and no significant effect (P > 0.05 ) on the texture. Award kecombrang flower powder at dose of 6% show broiler meat quality better when compared with other treatments. (Keywords : kecombrang flower powder, broiler meat, texture, water holding capacity and, cooking loss).